FROM INSIGHT TO IMPACT: A FRAMEWORK FOR INTEGRATING REAL-TIME SOCIAL LISTENING INTO STRATEGIC MARKETING DECISION CYCLES - Christina Maria Attonete; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This study examines the integration of real-time social listening into strategic marketing decision cycles within contemporary digital marketing environments. The research explores how organizations utilize consumer-generated data from social media platforms to support marketing intelligence, customer responsiveness, and organizational agility. Using a narrative literature review approach, the study synthesizes theories and empirical findings related to social listening, marketing analytics, agile marketing, and strategic decision-making. The findings indicate that real-time social listening enables organizations to detect emerging trends, analyze consumer sentiment, and improve responsiveness to changing market conditions. The study also identifies major integration challenges, including data overload, siloed organizational structures, and technology adoption barriers that limit the strategic use of social listening insights. Furthermore, the research demonstrates that integrating social listening into marketing decision cycles enhances decision-making speed, campaign optimization, and customer engagement. The proposed framework emphasizes the importance of combining technological capabilities, organizational alignment, and strategic interpretation to transform digital insights into actionable marketing strategies. Overall, the study contributes to digital marketing and strategic management literature by providing a comprehensive framework for integrating real-time social listening into organizational decision-making processes and improving long-term marketing effectiveness.